Penerapan Evaluasi Pembelajaran Membaca di Kelas Tinggi - Rambe, Riris Nurkholidah; Putriana, Alda; Siregar, Amelia Rika Fadillah; Siregar, Rahma Fadillah; Daulay, Siti Amalia; Napitupulu, Zumiati Syarah Br (Lembaga Yasin AlSys, 2023)
One of the competencies that must be mastered by a teacher is evaluation learning. This competence is in accordance with the duties and responsibilities of teachers in learning activities namely evaluating learning, including conducting an assessment of the process and learning outcomes. Ability to evaluate Learning is a basic ability that absolutely must be owned by every student Teacher. In terms, there are several definitions formulated by experts. However, from some of these opinions it can be concluded that in essence evaluation is a systematic and ongoing process to determine the quality (value and meaning) of something (goals, activities, decisions, performance, processes, people, or objects) based on certain considerations and criteria in the framework to make a decision. When the word is connected with the word learning, the meaning is the process of determining services, values or benefits of learning activities through assessment activities and/or measurement. In carrying out learning evaluation, there are at least three conditions that must be met are valid, reliable and practical. While the instructions in compiling a test/evaluation tool is that the test must have a level of validity and good reliability. Evaluation techniques are test techniques and techniques notes.